Psychological distress and job involvement among dental surgeons in Lagos, Nigeria. - A. O. Coker; B. O. Ogunbanjo; O. A. Awotile; M. E. Sorunke; O. O. Onigbinde; A. O. Adewuya; B. A. Ola (Nigerian Dental Association, 2008)
Objective: Studies on job involvement and mental health have mainly been carried out among Caucasian populations. Similar studies are lacking in Nigeria.This study was aimed at investigating psychological distress and job involvement among dental surgeons working in Lagos, Nigeria.  Method: Thirty-eight dental surgeons working at the two teaching hospitals in Lagos State, Nigeria were invited to participate in this study. The dental surgeons completed three selfadministered questionnaires, a questionnaire on demographics, Job Involvement th Inventory (JII) and the 12 version of the General Health Questionnaire (GHQ-12). Results: Among the dental surgeons surveyed, 18.42% had a GHQ score of 4 and above which indicated that they were at increased likelihood of having a psychological disorder. As regards job involvement, 66.67% of the dental surgeons scored high on the JII; this shows that the dental surgeons were poorly involved emotionally in their jobs. Conclusion: The findings of this study showed that dental surgeons working in Lagos State manifest with certain degrees of psychopathology and majority of them were poorly emotionally involved in their job. There is a need for dental surgeons to acquire management science training and stress management skills  Soenhance service delivery.